Designation the Structural forms that derived from 4.2 -di- hydroxide benzaldehyde using chemical and physical methods - Adil Azooz; Mohammed Al-Noayme (College of Education for Pure Sciences, 2009)
Abstract The work is involved with the preparation of 2,4- dihydroxy- benzaldehyde as a mother compound. Then after, the mentioned aldehyde is converted into fourteen imines derivatives in forms of Schiff bases and oxime, by its reaction with an appropriate primary amines as hydroxylamine hydrochloride and o,m , p-aminophenols and others. The structures of these prepared imines are confirmed by using some physical methods such as U.V, I.R spectra and melting points for all Schiff bases and theirs greater solubilities in water are attributed to their presence in zwitter ions forms.